JURIDICAL REVIEW IN EFFORT TO COMMAND OFFENSIVE CRIMINAL ACTIONS PERFORMED BY UNDERAGE CHILDREN (CASE STUDY DECISION NO. 563/PID.SUS/2021/PN LBP) - Anisa Fitri; Mahzaniar Mahzaniar (Fox Justi : Jurnal Ilmu Hukum, 2022)
In writing this thesis the author discusses the juridical review in an effort to overcome immoral crimes committed by minors. This is motivated because the author feels the importance of protecting children in legal matters. On the basis of looking at the condition of the surrounding environment and the circumstances in which the violation of this law is increasingly rampant. This study aims to find out about how the process of tackling immoral crimes against children as the next generation. This research was conducted in Deli Serdang Regency by choosing an agency that has a connection with this problem having its address at the Lubuk Pakam District Court Class IA Jl. General Sudirman No. 58 Lubuk Pakam, Postal Code: 20512, North Sumatra. The type of research used is juridical research, namely legal research conducted based on norms and rules and legislation, especially those relating to the implementation of Law no. 35 of 2014 concerning Child Protection. The results of the study discuss the factors that cause immoral crimes in children, namely family factors, environmental factors, educational factors and social media technology development factors. Completion of cases of judges' decisions on perpetrators of immoral criminal cases. Efforts made in tackling immoral crimes against children, namely legal counseling are very important, given that in general criminals are criminals. Especially immoral crimes against children is the level of legal awareness is still relatively low, so that with this outreach activity, it is hoped that they can understand and realize that immoral crimes against children are unlawful acts and are detrimental to society, which are threatened by law. Then repressive efforts in tackling immoral crimes against children. The repressive action is carried out by arresting and legally processing the perpetrators of immoral crimes against children in accordance with applicable legal regulations.